TINDAK TUTUR ILOKUSI DIREKTIF DALAM ANIME SPIRITED AWAY KARYA HAYAO MIYAZAKI - Sri Meizi Yurita Meizi Yurita; Zuli Laili Isnaini Laili Isnaini; Yenny Aristia Nst Aristia Nst (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aimed to find out kind of illocutionary speech acts in anime Spirited Away by Hayao Miyazaki. Besides that, it also aimed describe the purpose of this illocutionary speech acts. Theory that used were Searle theory to find out kind of illocutionary speech act and Leech theory the purpose of it. The method was descriptive as to describe the data using word or sentences. The data was collected from Japan’s anime Spirited Away. The result showed that there were 60 data of illocutionary speech acts and divided into 5 kinds, namely (1) requestives including 3 data for persuading, 4 data for requesting, and 5 data for asking (2) questions including 16 data for questioning (3) requirements including 19 data for ordering, 1 data for instruction, 2 data for directing, and 1 data for demanding (4) permissives including 1 data for letting go (5) advisories including 8 data for warning. There was also found (1) 34 data purposes of collaborative speech acts, (2) 21 data purpose of convivial speech acts, (3) 15 purpose of competitive. Key Words: speech acts, illocutionary, directive